Vegetation cover and plant diversity on cold climate green roofs ... - Lönnqvist, Joel; Blecken, Godecke-Tobias; Viklander, Maria (Dryad, 2019)
Both vegetation abundances and community compositions play important roles for the functions of green roofs (e.g. stormwater retention, habitat provision, aesthetic appearance). However, green roof vegetation can change significantly over time, which may consequently affect the functions related to them. This study investigated vascular plant covers and species compositions on 41 roof sections located in Sweden’s subarctic and continental climate zones. For the roof sections with a known originally intended vascular plant composition (n=32), on average 24±9% of the intended species were present in surveys while unintended species made up 69±3% of the the species found. The Intended species dominated plant cover (93±3%) and Sedum acre (58±36% cover) was the most commonly found species. As revealed in previous studies, substrate depth had a positive relationship with plant cover and species richness. The vascular plant cover of the roofs in this study was not related to species richness as hypothesized but ... : During the vegetation survey, the following variables were recorded. When referring to their use as modelling parameters (and for convenience here) these variables are italicized: Species richness (number of vascular plant species detected on a roof section) Cover of individual vascular plant species in quadrats (%) Total vascular plant cover (%) Total moss cover (%) Substrate depth (mm) Age (years) Roof area (m2) Roof width (m) Roof length (m) Aspect (in cardinal direction: North, East, South or West) Stratified random sampling was used to estimate the vegetation cover on the selected roof sections. For this, sampling quadrats (each consisting of a 1×1 m wooden frame) were evenly spread along transects on each roof section, avoiding edge zones such as ventilation shafts. The number of quadrats used on each section (3-54) was limited by the size of roof sections. The quadrats covered a minimum of 6% of the roof section surfaces and vegetation cover was estimated visually with grids in each quadrat. The ...